Internal Audit as a Tool for Securing Public Investment Projects in Emerging Economies - MUSTAPHA EZZAYRI; M’BARKA EL GHAZALI (African Scientific Journal, 2025)
Abstract: This study investigates the role of internal auditing as a tool for securing public investment projects in emerging economies, focusing on Morocco, India, Brazil, and Vietnam over the period 2010–2024. Using the Autoregressive Distributed Lag (ARDL) approach, the research examines both the short-run and long-run relationships between public investment project performance, internal audit indicators, governance quality, and macroeconomic stability. Panel unit root and cointegration tests confirm the presence of stable long-term relationships among the variables, while Error Correction Model (ECM) estimations reveal rapid adjustment dynamics toward equilibrium. The empirical results show that internal auditing and governance exert significant and sustained positive effects on investment performance, with governance acting as a structural enabler of audit effectiveness. Macroeconomic factors, though exerting smaller coefficients, remain statistically relevant in ensuring a conducive environment for long-term project success. Policy recommendations emphasize strengthening audit frameworks, enhancing governance structures, and integrating macroeconomic stability into investment planning, with tailored strategies for each national context. The findings contribute to the literature on public investment efficiency and institutional reforms in emerging markets, offering actionable insights for policymakers and development practitioners. Keywords: Internal auditing; Public investment performance; Governance; ARDL model; Emerging economies; Morocco; India; Brazil; Vietnam; Macroeconomic stability; Error correction model; Institutional reforms; Policy recommendations.